PENGARUH AUDIT LAG, UKURAN KAP DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN: Studi Empiris pada Perusahaan Energy Yang Terdaftar Di Bursa Efek Indonesia - Shanti Clara; Desy Purwasih (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of the saudit lag, KAP size and prior opinion on going concern audit opinion acceptance. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange in 2016-2020. This research is an associative study with a quantitative approach. The research sample was taken using purposive sampling technique so that 13 companies were selected as research samples and the period of the year studied was 5 years, from 2016 to 2020 so that there were 65 samples. The data used are taken from audited financial reports and annual reports published by each company studied. The data analysis technique used descriptive statistics and logistic regression analysis, The results show partially audit lag and audit quality has no effect on going concern audit opinion acceptance, and prior opinion has an effect on going concern audit opinion acceptance. Simultaneously, audit lag, kap size and prior opinion had an effect on going concern audit opinion acceptance